Pregnancy and neonatal outcomes among women with early-onset colorectal cancer: a nationwide case–control studyResearch in context - Yin Cao; Stephanie Zhao; Tomas S. Bexelius; Jonas Söderling; Mengyao Shi; Bjorn Roelstraete; Barbara B. Warner; Olof Stephansson; Jonas F. Ludvigsson (EClinicalMedicine, 2023)
Summary: Background: Early-onset colorectal cancer has risen worldwide, leaving more women with colorectal cancer at reproductive ages. We aimed to investigate the risk of adverse pregnancy and neonatal outcomes among women with early-onset colorectal cancer. Methods: We conducted a nationwide, matched case–control study of maternal/pregnancy outcomes including pre-eclampsia and Cesarean delivery (C-section) as well as neonatal outcomes including preterm birth among 207 births in women with early-onset colorectal cancer (ages 18–49) and 1019 births in women without colorectal cancer in Sweden (1992–2019). Early-onset colorectal cancer cases were identified through the Cancer Register, and outcome data were retrieved through linkage to Medical Birth Register and National Patient Register. Using conditional logistic regression, we estimated multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs). Findings: Between Jan 1, 1992, and Dec 31, 2019, women with early-onset colorectal cancer who gave birth had increased odds of pre-eclampsia (7.2% vs 3.2%; OR = 2.52, 95%CI = 1.25–5.08), any C-section (24.6% vs 19.4%; OR = 1.43, 95%CI = 1.00–2.06), particularly emergency C-section (17.4% vs 10.5%; OR = 1.79, 95%CI = 1.17–2.75), after adjustment for maternal education level, country of birth, body mass index and smoking in early pregnancy, and comorbidities. Maternal history of early-onset colorectal cancer was also associated with offspring preterm birth (12.1% vs 5.2%; OR = 2.31, 95%CI = 1.34–3.99), delineated as spontaneous (OR = 1.06, 95%CI = 0.47–2.39) or medically-indicated preterm birth (OR = 4.48, 95%CI = 2.05–9.79). There was no increased risk of congenital malformation or small for gestational age birth. Interpretation: In this population-based study, maternal history of early-onset colorectal cancer was associated with risk of both adverse pregnancy (pre-eclampsia, C-section) and neonatal outcomes (preterm birth). Funding: US National Institutes of Health, Swedish Society of Medicine, Swedish Cancer Foundation.